Anti‐inflammatory effect from extracts of Red Chinese cabbage and Aronia in LPS‐stimulated RAW 264.7 cells. Issue 4 (24th February 2020) - Kwak, Jung Hyun; Kim, Yoonji; Ryu, Soo In; Lee, Minho; Lee, Hyo‐Jeong; Lim, Yong Pyo; Paik, Jean Kyung
Abstract: A chronic inflammatory environment facilitates tumor growth and proliferation. Fruits and vegetables are important sources of anthocyanins, polyphenols, and other biologically active substances that can favorably affect the pathogenesis of cancer. The objective of the study was to investigate the anti‐inflammatory effects of Red Chinese cabbage (RC) and mixture of commercial Red Chinese cabbage leaves and Aronia fruits (ARC) in LPS‐stimulated RAW 264.7 cells. The RAW 264.7 cells were cultured and measured the cytotoxicity by using an MTT assay. The inflammatory markers, such as nitrite, IL‐6, and TNF‐alpha expression, were evaluated using ELISA, and protein expression of inflammatory markers like iNOS and COX‐2 was analyzed using Western blot. MTT assays showed that pretreatment of RAW 264.7 cells with RC and ARC did not change cell growth or cytotoxicity. We also found that ARC extracts reduced inflammation‐related biomarker (TNF‐a, IL‐6, and NO) production and gene expression (iNOS, COX‐2). Our results suggested that ARC has good anti‐inflammatory properties compared with RC that maybe used as potential nutrients for treating inflammatory diseases. Abstract : The extracts of Red Chinese cabbage and Aronia have good anti‐inflammatory properties compared with Red Chinese cabbage that maybe used as potential nutrients for treating inflammatory diseases.